Mortar cohesión. The effect of additives - Kittll, P.; Castro, J. H. (Materiales de Construcción, 1975)
This study was concerned with the hydration of clinker compounds in the presence of different additives; it appeared that accelerating additives, such as calcium chloride and silicic acid, produce longer fibers of tobermorite, whereas inhibitors, such as sugar, produce shorter fibers of tobermorite. This same effect was observed in the hydration of anhydrite, in which large crystals of gypsum were produced in the presence of sodium sulphate. So the cohesion in mortars of cement and anhydrite is explained in terms of the role of fibers.